Employing defined bioconjugates to generate chemically functionalised gold nanoparticles for in vitro diagnostic applications. Issue 27 (30th June 2021) - Richards, Daniel A.; Thomas, Michael R.; Szijj, Peter A.; Foote, James; Chen, Yiyun; Nogueira, João C. F.; Chudasama, Vijay; Stevens, Molly M.
Abstract : Herein we report a versatile method for introducing functionality to gold nanoparticles by exploiting the strong interaction between chemically functionalised bovine serum albumin ( f -BSA) and citrate-capped gold nanoparticles (AuNPs). Abstract : Novel methods for introducing chemical and biological functionality to the surface of gold nanoparticles serve to increase the utility of this class of nanomaterials across a range of applications. To date, methods for functionalising gold surfaces have relied upon uncontrollable non-specific adsorption, bespoke chemical linkers, or non-generalisable protein–protein interactions. Herein we report a versatile method for introducing functionality to gold nanoparticles by exploiting the strong interaction between chemically functionalised bovine serum albumin ( f -BSA) and citrate-capped gold nanoparticles (AuNPs). We establish the generalisability of the method by introducing a variety of functionalities to gold nanoparticles using cheap, commercially available chemical linkers. The utility of this approach is further demonstrated through the conjugation of the monoclonal antibody Ontruzant to f -BSA–AuNPs using inverse electron-demand Diels–Alder (iEDDA) click chemistry, a hitherto unexplored chemistry for AuNP–IgG conjugation. Finally, we show that the AuNP–Ontruzant particles generated via f -BSA–AuNPs have a greater affinity for their target in a lateral flow format when compared to conventional physisorption, highlighting the potential of this technology for producing sensitive diagnostic tests.